Analysis of Transparency and Accountability of Village Fund Management in Bengkalis Sub-district - Muhammad Luthfi Iznillah; Yesi Mutia Basri (Journal of Economics, Business, and Government Challenges, 2018)
The existence of village autonomy makes villages free to manage their own household, including in the case of village financial management. The amount of funds obtained by the village demands the village government to be able to manage its finances well, because based on the Minister of Home Affairs regulation no 113 2014 village finances are managed on the basis of transparent, accountable, participatory principles and carried out in an orderly and disciplined budget. Thepurpose of this study is to determine the level of Transparency and Accountability and how the management of village finances in the district Bengkalis. This research was conducted in Bengkalis District with total 28 villages using Mixed research method. The population in this study were 28 villages and using the Saturated sampling technique. The results of this study indicate that the level of Transparency and Accountability for each Financial Management Stage from Planning, Implementation, Administration, Reporting and Accountability is at the lowest value of 86.64% to 100%, meaning that in managing the financial village of Bengkalis Sub-district has fulfilled the Principle of Transparency and Accountability. Meanwhile, qualitatively there are various obstacles in each stage,ranging from regulatory changes, natural constraints, quality of human resources, even until the delay. However, the local government continues to improve this condition by always providing assistance to the village government, one of which is in the form of training so that village officials as the spearhead of village finance managers have good capacity so that they can manage the village finances well andexpected to give a significant impact to the welfare of rural communities.